2000
DOI: 10.1006/dbio.2000.9799
|View full text |Cite
|
Sign up to set email alerts
|

Tracing the Progeny of the Aortic Hemangioblast in the Avian Embryo

Abstract: A population of hematopoietic progenitors becomes committed within the embryo proper in the floor of the aorta (P-Sp/AGM in the mouse). In birds, this first aspect of intraembryonic hematopoiesis is prominent during embryonic day 3 (E3) as endothelium-associated "intra-aortic clusters." Between E6 and E8, diffuse hematopoiesis then occurs as "para-aortic foci" located in the dorsal mesentery ventral to the aorta. These foci are not associated with endothelium. Whether these two hematopoietic cell populations a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
101
0
3

Year Published

2003
2003
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 145 publications
(110 citation statements)
references
References 50 publications
3
101
0
3
Order By: Relevance
“…Chick/quail and chick/chick chimera studies (Beaupain et al, 1979;Dieterlen-Lievre, 1975;Dieterlen-Lievre et al, 1976;Lassila et al, 1978;Lassila et al, 1982;Martin et al, 1978) and chick/chick parabiotic studies (Metcalf and Moore, 1971;Moore and Owen, 1965; indicated that, at least during the first few days of definitive erythrocyte generation, the source of cells is mainly yolk sac-derived. At about the same time, if not earlier, intraembryonic hematopoietic cells have been observed in association with the dorsal aorta (DieterlenLievre and Martin, 1981;Jaffredo et al, 2003;Jaffredo et al, 2005;Jaffredo et al, 2000;Jaffredo et al, 1998;Jordan, 1916;Nagai and Sheng, 2008;Olah et al, 1988;Pardanaud et al, 1996). A number of questions can be asked, for instance, about whether dorsal aorta-derived hematopoietic cells undergo definitive erythropoiesis either in circulation or in the yolk sac niche; whether yolk sac-derived hematopoietic cells can find their way to the dorsal aorta; and what is the exact type of cells from the yolk sac that contribute to early definitive erythropoiesis.…”
Section: Transition From Primitive To Definitive Wavementioning
confidence: 87%
“…Chick/quail and chick/chick chimera studies (Beaupain et al, 1979;Dieterlen-Lievre, 1975;Dieterlen-Lievre et al, 1976;Lassila et al, 1978;Lassila et al, 1982;Martin et al, 1978) and chick/chick parabiotic studies (Metcalf and Moore, 1971;Moore and Owen, 1965; indicated that, at least during the first few days of definitive erythrocyte generation, the source of cells is mainly yolk sac-derived. At about the same time, if not earlier, intraembryonic hematopoietic cells have been observed in association with the dorsal aorta (DieterlenLievre and Martin, 1981;Jaffredo et al, 2003;Jaffredo et al, 2005;Jaffredo et al, 2000;Jaffredo et al, 1998;Jordan, 1916;Nagai and Sheng, 2008;Olah et al, 1988;Pardanaud et al, 1996). A number of questions can be asked, for instance, about whether dorsal aorta-derived hematopoietic cells undergo definitive erythropoiesis either in circulation or in the yolk sac niche; whether yolk sac-derived hematopoietic cells can find their way to the dorsal aorta; and what is the exact type of cells from the yolk sac that contribute to early definitive erythropoiesis.…”
Section: Transition From Primitive To Definitive Wavementioning
confidence: 87%
“…The first in vivo experimental support came much later, from lineage tracing of endothelium in the chick embryo [25,26]. More recently, lineage-tracing studies in which Cre recombinase was expressed under the regulatory control of the endothelial marker VE-Cadherin (VECadh) lent further support to this model [27,28].…”
Section: Identification Of Hemogenic Endotheliummentioning
confidence: 99%
“…Alternatively, intraembryonic hematopoietic cell production is thought to occur through a completely different process involving the production of HCs by a mature, already differentiated endothelium. In vivo production of HCs by ECs has been demonstrated at the level of the aorta in the avian model 22,23 and is strongly assumed for the mouse AGM. 35 Consistent with data from gene inactivation in mice, several genes have been identified that affect one lineage but not the other.…”
Section: Definitive Erythropoiesis Emerged Through An Ec Intermediatementioning
confidence: 99%
“…Two different tracers were used: Ac-LDL, which is specifically and rapidly endocytosed by ECs, and nonreplicative retroviral vectors carrying a lacZ reporter gene. 22,23 We have applied the Ac-LDL-mediated tracing method to tag the mouse vascular tree in vivo when definitive hematopoiesis occurred. We have designed a system comprising a step of Ac-LDL intracardiac delivery followed by a whole-embryo culture period.…”
Section: Introductionmentioning
confidence: 99%